Welcome to the year 2026 and volume 29: Time for the “Know thy eGFR and urine protein – and act” campaign - Assounga, Alain G (African Journal of Nephrology, 2026)
On behalf of the Editorial Board of the African Journal of Nephrology (AJN), I wish all AJN contributors and readers a very happy and productive year 2026. Last year, following AJN accreditation with the CAMES (Conseil Africain et Malgache pour l’enseignement Supérieur), we witnessed a significant increase in the submission of French manuscripts. To the contributors of these French manuscripts, we thank you for your submissions, which make AJN a truly bilingual journal. This year, we aim to move AJN to a new hosting platform that will enable us to apply for accreditation for Scopus and PubMed. We take this opportunity to thank all contributors for the large number of submitted manuscripts, and reviewers for evaluating these manuscripts and providing valuable feedback. In volume 28, we noted several highlights: a scoping review by Ngema et al. revealed the extent of depression in dialysis patients and Davidson et al. reported on the stability of the peritonitis rate in Cape Town despite extreme conditions such as a severe drought and the COVID-19 pandemic. Finally, Ndinya et al. reported that unexplained hyperkalaemia is associated with low rates of in-hospital death. This year, World Kidney Day will take place on 12 March 2026 with the following theme: “Kidney health for all – caring for people, protecting the planet”. Several nephrology bodies have recommended that serum urea and creatinine results be reported together with estimated glomerular filtration rate (eGFR), estimated using widely accepted equations. We should commend commercial laboratories for routinely providing eGFR results. In HIV medicine, patients are educated to be informed about their CD4 count and viral load. In nephrology, eGFR and proteinuria provide an essential evaluation of kidney function. Each adult should know their eGFR and the status of their proteinuria, with these tests being done at least annually. We need to democratise this knowledge, empower patients to own it and help them participate in the management of their kidney function, as shown in an algorithm adapted from the International Society of Nephrology [1]. Let us give them the tools to help themselves. With a strategy that includes a healthy diet, inhibition of the renin-angiotensin-aldosterone system and the control of comorbidities, we can delay or avoid dialysis for at least two-thirds of patients. Therefore, let us start the “Know thy eGFR and urine protein – and act” campaign.